2021
DOI: 10.1007/s00395-021-00847-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal guidance proteins in cardiovascular inflammation

Abstract: Cardiovascular pathologies are often induced by inflammation. The associated changes in the inflammatory response influence vascular endothelial biology; they complicate the extent of ischaemia and reperfusion injury, direct the migration of immune competent cells and activate platelets. The initiation and progression of inflammation is regulated by the classical paradigm through the system of cytokines and chemokines. Therapeutic approaches have previously used this knowledge to control the extent of cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 101 publications
(130 reference statements)
0
12
0
Order By: Relevance
“…Finally, some studies have implicated netrin-1 signaling via the Adora2b in the treatment of Aspergillus fumigatus infection of the cornea (Zhou et al, 2019). Taken together, these studies during inflammation or ischemia and reperfusion provide evidence for the netrin-Adora2b link in attenuating inflammation, promoting the resolution of inflammation and rescuing organ function (Aherne et al, 2013;Mirakaj and Rosenberger, 2017;Keller et al, 2021).…”
Section: Other Examples For the Netrin-adora2b Link During Inflammato...mentioning
confidence: 89%
See 2 more Smart Citations
“…Finally, some studies have implicated netrin-1 signaling via the Adora2b in the treatment of Aspergillus fumigatus infection of the cornea (Zhou et al, 2019). Taken together, these studies during inflammation or ischemia and reperfusion provide evidence for the netrin-Adora2b link in attenuating inflammation, promoting the resolution of inflammation and rescuing organ function (Aherne et al, 2013;Mirakaj and Rosenberger, 2017;Keller et al, 2021).…”
Section: Other Examples For the Netrin-adora2b Link During Inflammato...mentioning
confidence: 89%
“…The properties and functions on netrin-1 within the CNS as neuronal guidance molecule make it an ideal candidate for also guiding inflammatory cell trafficking events. In fact, several other neuronal guidance molecules (Konig et al, 2012;Mirakaj et al, 2012;Kohler et al, 2013;Kohler et al, 2020) have been implicated in immunomodulation and coordination of inflammatory events or resolution of inflammation (Mirakaj and Rosenberger, 2017;Keller et al, 2021). The unique characteristic of netrin-1 to repulse or abolish the attraction of developing neuronal cells via signaling events through the UNC5b receptor makes it a perfect candidate gene for coordinating inflammatory cell migration (Figure 3).…”
Section: Netrin-1 As a Guidance Cue During Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the present studies demonstrate immediate signaling effects by treating mice with recombinant netrin, it appears more unlikely that the observed cardioprotection is related to preconditioning or education of myeloid progenitor cells. While the current studies are focused on functional roles of the signaling molecule netrin-1 during myocardial IR injury, other neuronal guidance molecules have been implicated in orchestrating inflammatory endpoints as well ( Keller et al, 2021 ; Mirakaj and Rosenberger, 2017 ). For example, a recent study showed elegantly that RBC-derived semaphorin 7A promotes thromboinflammation in an in situ model of murine myocardial IR injury ( Köhler et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Netrin-1 was originally described as a neuronal guidance molecule important in brain development (47). However, more recent studies implicate netrin in orchestrating inflammatory events, including myocardial inflammation (48). Moreover, other studies had implicated HIF1A in the transcriptional regulation of netrin-1 during hypoxia, and identified netrin-1 as a classic HIF-target gene (44, 49).…”
Section: Resultsmentioning
confidence: 99%